Revising the M235T Polymorphism Position for the AGT Gene and Reporting a Modifying Variant in the Brazilian Population with Potential Cardiac and Neural Impact - Lemos, R. R.; de Lima, S. G.; da Cunha, J. E. Gomes; Oliveira, D. F.; de Souza, M. B. Rodrigues; Ayres, C. F. J.; Albuquerque, M. F. P. M.; Oliveira, J. R. M. (Journal of molecular neuroscience, 2012)
There is a growing need to curate the overwhelming amount of sequencing data which is available in many public databases. For instance, new information shows that the M235T polymorphism at the angiotensinogen gene (AGT) is actually positioned at the position corresponding to the amino acid 268 and not 235. This polymorphism is filled as rs699 in the NCBI SNP database and results in the synthesis of a threonine (T) instead of a methionine (M). It has been widely studied and associated as an important risk factor for several vascular and neuropsychiatric conditions. We faced this new situation during the targeted sequencing of 360 chromosomes from Brazilian subjects studied for the M235T polymorphism, leading to the identification of a novel variation (rs141900991). This report explores the potential impact of such a dinucleotide variation, which promotes the change of alanine (A) to serine (S) at the AGT protein structure (A237S). Considering the previous M268T variation at the four possible haplotypes combined (MA, MS, TA and TS), we performed a comparative hydrophobicity simulation, using the Kyte–Doolittle algorithm, available at the CLB Bio workbench, in the four possible haplotypes. Additional simulations were performed using the programs PolyPhen, I-Mutant and SIFT, in order to evaluate the pathogenicity of both mutations. The predicted hydrophobicity decreases of a similar magnitude, with both MS and TA haplotypes, but the presence of both variations induces a major decrease in hydrophobicity, suggesting a cumulative effect, with possible modifying effect since that this variation per se would limit the hydrophobicity range and the latter chances in finding significant phenotype differences. A better characterization of this kind of variant is particularly important because the current genome wide scan analyses in complex disorders with cardiac or neural etiology are not generating reliable findings, especially if we consider the huge investment with such approach. Additional and unknown variations like this one, with potential modifying effect, might be more common than previously expected.